Rapport-Threatening Behaviors in Instagram Interactions - Reski, Reski; Syam, Nur Ina; Rusdiah, Rusdiah (Action Research Literate, 2024)
Social media has been widely used by many people nowadays. Chatting, playing games, calling friends and relatives, and even making an appointment for a date or reunion with some old friends can now easily be organized in social media. With those many uses, each social media platform has some community standards to regulate the interaction to avoid any violation or offence that may threaten the harmonious atmosphere in the interaction. Despite that, some harsh words, rude comments, and negative attitudes can still be easily found in social media interactions. This research investigates those rapport-threatening behaviors by analyzing how they are expressed and whether they are threatening the social media users’ rapport or not. The research finds that there are several rapport-threatening behaviors in the interactions on Instagram which are sarcasm, insult, criticism, profanity, challenge, and even emoji use.